4y-9(3y-2)=

Simple and best practice solution for 4y-9(3y-2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4y-9(3y-2)= equation:


Simplifying
4y + -9(3y + -2) = 0

Reorder the terms:
4y + -9(-2 + 3y) = 0
4y + (-2 * -9 + 3y * -9) = 0
4y + (18 + -27y) = 0

Reorder the terms:
18 + 4y + -27y = 0

Combine like terms: 4y + -27y = -23y
18 + -23y = 0

Solving
18 + -23y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-18' to each side of the equation.
18 + -18 + -23y = 0 + -18

Combine like terms: 18 + -18 = 0
0 + -23y = 0 + -18
-23y = 0 + -18

Combine like terms: 0 + -18 = -18
-23y = -18

Divide each side by '-23'.
y = 0.7826086957

Simplifying
y = 0.7826086957

See similar equations:

| Y=-.01x^2+.5x+3 | | 32+6x=53 | | 118-3.8t=7.36-1.9t | | (16x-6)=180 | | .26(2.39x-4.91)=10.64 | | 6x+9x+x=180 | | -2x-4(7x-2)=-6x+8 | | 0.125(6+n)=2.50 | | 25x^5+10x^4-20x= | | sqrt(15x)=3x | | 7p-(-3p)+(-5)=15 | | 6x+32=53 | | 0=-16t^2+368 | | -4x-27=7 | | 25x^5+10x^4-20= | | =19-16(-9+17k) | | 3x+8=-3+4c | | 2l-4s=50 | | (x^2)(p^2)+xyp-6y^2=0 | | 1-4p=y | | X^2+2x-9=180 | | 10x^2+14x= | | 10a-7+9=26 | | (5x+30)=7x | | T^2+14T-40=0 | | 5r+32=-7(3+7r)+r | | 2(11+5x)-9= | | 11x^2+2x-34=0 | | 18f-11=48 | | (4x+8)=51 | | 63-x=2x+8n | | (X-8)(x-20)=180 |

Equations solver categories